Pengaruh Teori Belajar Vygotsky terhadap Kemampuan Berpikir Kritis Siswa Madrasah Ibtidaiyah - Desi Khoiriah; Nurliati Nasution; Nabilah Agustina; Adi Mukti (PT. Willy Print Art, 2025)
Critical thinking skills are essential competencies in 21st century education, especially at the basic education level such as Madrasah Ibtidaiyah (MI). Vygotsky's learning theory, with the main concepts of Zone of Proximal Development (ZPD) and scaffolding, emphasises the importance of social interaction in the learning process. This study aims to analyse the effect of applying Vygotsky's theory on improving the critical thinking skills of MI students. The method used is a literature study of various related research and literature in the last 10 years. The results of the analysis show that learning approaches based on Vygotsky's theory, such as inquiry-based and collaborative learning, can improve the critical thinking skills of MI students. The implication of this finding is the importance of integrating Vygotsky's principles in learning strategies in MI to develop students' critical thinking skills.